2020
DOI: 10.3389/fnhum.2020.581652
|View full text |Cite
|
Sign up to set email alerts
|

The Vividness of Motor Imagery Is Correlated With Corticospinal Excitability During Combined Motor Imagery and Action Observation

Abstract: The present study aimed to investigate the relationship between motor imagery (MI) assessment (ability and quality) and neurophysiological assessment [transcranial magnetic stimulation (TMS)-induced motor-evoked potentials (MEPs)] during combined MI and action observation (AO; MI + AO). Sixteen subjects completed an MI task playing the piano with both hands, and neurophysiological assessment was performed during the MI task. The Movement Imagery Questionnaire-Revised was adopted to evaluate MI ability, while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
(49 reference statements)
2
17
0
Order By: Relevance
“…In the MI condition, they were asked to kinesthetically imagine that they were walking without performing voluntary contraction. We provided the following instruction: “ Please imagine kinesthetically that you are walking without performing voluntary muscle contraction .” We confirmed that the participants could perform the MI using a VAS [ 31 ]. After completing the MI, they were asked to make a mark on a 10-cm-long VAS line on paper, which provided the VAS score.…”
Section: Methodssupporting
confidence: 61%
See 1 more Smart Citation
“…In the MI condition, they were asked to kinesthetically imagine that they were walking without performing voluntary contraction. We provided the following instruction: “ Please imagine kinesthetically that you are walking without performing voluntary muscle contraction .” We confirmed that the participants could perform the MI using a VAS [ 31 ]. After completing the MI, they were asked to make a mark on a 10-cm-long VAS line on paper, which provided the VAS score.…”
Section: Methodssupporting
confidence: 61%
“…Thus, we hypothesized that the ability to perform MI of walking increases post-intervention. Our hypotheses were tested using a visual analog scale (VAS) [ 31 ], and we measured the corticospinal excitability during MI of walking [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…To assess the effect on cortical oscillatory activity, resting-state EEG was recorded before and after each stimulation condition. Finally, previous research has also demonstrated a significant positive relationship between the self-reported kinesthetic vividness of MI and the MI-induced change in corticomotor excitability (Williams et al, 2012;Vasilyev et al, 2017;Moriuchi et al, 2020) and intracortical excitability (Lebon et al, 2012). Therefore, the Kinesthetic and Visual Imaging Questionnaire (KVIQ) (Malouin et al, 2007) was included in experiment 2 to assess the participants' MI ability, to explore if any relationship was present between visual and kinesthetic MI ability and the change in cortical oscillatory activity following state-dependent PEMS.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, studies using transcranial magnetic stimulation (TMS) have indicated that the corticospinal excitability of related muscles increases during MI (Fadiga et al, 1999;Hashimoto & Rothwell, 1999;Lebon et al, 2019;Stinear & Byblow, 2003), the timing of which is similar to that of ME (Kumru et al, 2008), and the degree of excitability is reported to be higher than that at rest and less than that during ME (Bouguetoch et al, 2020;Kumru et al, 2008;Lebon et al, 2019;Stinear & Byblow, 2003). However, the change in corticospinal excitability during MI as demonstrated by previous studies (Fadiga et al, 1999;Lebon et al, 2019;Stinear & Byblow, 2003, 2004 indicates that there are many temporal measurement points during MI, and these changes in excitability with time, during MI, remain unclear (Bouguetoch et al, 2020;Lebon et al, 2019;Moriuchi et al, 2020;Sakamoto et al, 2009;Stinear et al, 2006;Stinear & Byblow, 2003, 2004Takahashi et al, 2005;Tsukazaki et al, 2012). A study on timing in MI using mental chronometry reported that the timing in MI was nearly consistent with that in ME, but could increase or decrease depending on the complexity of the given situations and tasks (Guillot & Collet, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…The first is to understand the timing characteristics of MI and the changes in corticospinal excitability. The clarity of MI has been associated with the degree of corticospinal excitability, and as the MI becomes clearer, the degree of its enhancement is also increased (Moriuchi et al, 2020). Moreover, AO might increase the clarity of MI by combining AO and MI (AO + MI); this combination might increase the excitability more than AO or MI alone (Mouthon et al, 2015; Tsukazaki et al, 2012; Wright et al, 2014; Wright et al, 2016).…”
Section: Introductionmentioning
confidence: 99%